Hukum Tata Negara Darurat dalam Perspektif HAM : Dilema Antara Keamanan Negara dan Hak Asasi Manusia - M. Reza Saputra; Irwan Triadi; Taufiqurrohman Syahuri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research examines the dilemma between national security and human rights protection in the context of emergency constitutional law in Indonesia. Through a juridical-normative approach, this study analyzes the balance between state authority in dealing with emergencies and the obligation to protect citizens' human rights. The findings indicate that although the state can restrict human rights during emergencies, such restrictions must comply with the principles of necessity and proportionality and not violate non-derogable rights. Indonesia's experience implementing emergency constitutional law, such as in the cases of DOM Aceh and the COVID-19 pandemic response, demonstrates the importance of regulatory reform to create a more comprehensive legal framework in maintaining a balance between national security and human rights protection. This research recommends updating the State of Emergency Law to align with current developments and strengthen oversight mechanisms to prevent abuse of emergency powers.